SHANK2 establishes auditory hair bundle architecture essential for mammalian hearing - Han Seul Choi; Hyeyoung Park; Hyehyun Min; Kwan Soo Kim; Soo Min Kim; Jinan Li; Chang Liu; Hyuk Wan Ko; Min Goo Lee; Lei Song; Bo Zhao; Jinwoong Bok (Proceedings of the National Academy of Sciences, 2025)
The mammalian auditory system relies on the precise architecture of the hair cell stereociliary bundle for effective sound transduction. Each bundle consists of approximately 100 actin-filled stereocilia arranged in a three-row staircase pattern, forming a linear shape in inner hair cells (IHCs) and a V-shape in outer hair cells (OHCs), the latter geometry being a hallmark of the mammalian cochlea. While the initial development from uniformly distributed microvilli into stereociliary bundles is guided by lateral migration of the kinocilium, the mechanisms that establish the characteristic bundle architecture and its functional significance remain unclear. Here, we show that SHANK2, a protein implicated in synaptic function and autism spectrum disorders, is a critical regulator of bundle architecture. SHANK2 localizes to the medial apical surface of developing hair cells. This localization is regulated by the small GTPase RAP1, independently of known lateral (Gαi, GPSM2) or medial (aPKCζ, PARD6B) proteins. Hair cell-specific ablation of Shank2 or Rap1 disrupts bundle architecture while preserving key features essential for mechanotransduction. In particular, OHCs lose their unique bundle geometry and show impaired amplification, especially at high frequencies. Longitudinal studies further reveal that this architectural disruption leads to progressive bundle degeneration and hearing loss. These findings suggest that the characteristic bundle architecture, particularly the V-shaped geometry of OHCs, is essential for high-frequency hearing and long-term bundle integrity in the mammalian cochlea.